Hubungan kepemimpinan kepala sekolah dengan kepuasan guru di SDN Jatisampurna VIII Bekasi - Nani Hanifah (Sosio e-Kons, 2021)
The focus of this research is on the relationship between principal leadership and teacher satisfaction with the aim of knowing whether there is a relationship between principal leadership and teacher satisfaction at the school. The research method used is a quantitative method with a survey approach. The research instrument was a questionnaire filled out by 15 teachers as a research sample from 18 teachers as a population. From this instrument, it was calculated to obtain the value of the relationship (correlation coefficient) using the product moment correlation formula. Then the coefficient of determination is calculated using the formula (r) 2. After the r value was found, hypothesis testing was conducted by looking at the table of products moment values at the significant level ? = 0.05 by consulting the research results (r count) with the r table value. If r count> r table then Ho is rejected, it means there is a relationship, but if r count <r table then Ho is accepted, it means there is no relationship. Based on the results of the study, the value of r = 0.69 (high correlation) is linked to the product moment value table with a significance level of 5% with n = 15, namely 0.514, which means that the calculated r value is higher than the r table value, meaning that the null hypothesis (H0) is rejected, the hypothesis alternative (Ha) is accepted, namely that there is a relationship between principal leadership and teacher satisfaction at SDN Jatisampurna VIII of 47.61% (r2 = 0.4761